Tuning the Electronic Bandgap of Graphdiyne by H‐Substitution to Promote Interfacial Charge Carrier Separation for Enhanced Photocatalytic Hydrogen Production. (30th March 2021) - Li, Jian; Slassi, Amine; Han, Xu; Cornil, David; Ha‐Thi, Minh‐Huong; Pino, Thomas; Debecker, Damien P.; Colbeau‐Justin, Christophe; Arbiol, Jordi; Cornil, Jérôme; Ghazzal, Mohamed Nawfal
Abstract: Graphdiyne (GDY), which features a highly π‐conjugated structure, direct bandgap, and high charge carrier mobility, presents the major requirements for photocatalysis. Up to now, all photocatalytic studies are performed without paying too much attention on the GDY bandgap (1.1 eV at the G0 W0 many‐body theory level). Such a narrow bandgap is not suitable for the band alignment between GDY and other semiconductors, making it difficult to achieve efficient photogenerated charge carrier separation. Herein, for the first time, it is demonstrated that tuning the electronic bandgap of GDY via H‐substitution (H‐GDY) promotes interfacial charge separation and improves photocatalytic H2 evolution. The H‐GDY exhibits an increased bandgap energy (≈ 2.5 eV) and exploitable conduction band minimum and valence band maximum edges. As a representative semiconductor, TiO2 is hybridized with both H‐GDY and GDY to fabricate a heterojunction. Compared to the GDY/TiO2, the H‐GDY/TiO2 heterojunction leads to a remarkable enhancement of the photocatalytic H2 generation by 1.35 times under UV–visible illumination (6200 µ mol h −1 g −1 ) and four times under visible light (670 µ mol h −1 g −1 ). Such enhancement is attributed to the suitable band alignment between H‐GDY and TiO2, which efficiently promotes the photogenerated electron and hole separation, as supported by density functional theory calculations. Abstract : Adjusting the electronic bandgap of graphdiyne is the next step to move forward and expand the use of graphdiyne in photochemical reactions. The H‐substitution of graphdiyne maintains the large π‐conjugated structure and enables enlarging the bandgap, which is beneficial to target the construction of type II heterostructured photocatalysts for efficient charge carrier separation and H2 generation.